The promises and challenges of biofuels for the poor in developing countries: IFPRI 2005-2006 Annual Report Essay - von Braun, Joachim; Pachauri, R. K. (International Food Policy Research Institute, 2006)
In the past several years the changing world energy situation has generated intensive discussion about biofuels, much of it promising a source of environment-friendly energy that would also be a boon to the world’s farmers. At the same time skeptics argue that biofuel production will threaten food supplies for the poor and fail to achieve the environmental benefits claimed. Based on the analyses below, we conclude that in order to make a difference in the lives of poor people as both energy producers and consumers, and to make strong environmental and economic contributions, biofuel technology needs further advancement, and investments and policies facilitating agricultural innovation and trade will have to be considered.